The construction of a simple portable electromagnetic vibrator from commercially available components. (4th July 2018) - Dean, Timothy; Nguyen, Hoang; Kepic, Anton; Halliday, David
ABSTRACT: Since its introduction in the late 1950s, hydraulic vibrators have become the dominant source for land seismic surveys. The hydraulic vibrators typically used for commercial land seismic acquisition, however, are large, costly to operate and expensive to purchase. This inhibits their use for small‐scale and short‐duration surveys as well as Vibroseis research. In this paper we describe, in detail, the construction of a portable vibrator from commercially available components for a cost of less than US2, 000. Data shows that the vibrator is able to successfully transmit sweeps from 15 to 180 Hz with different spectral contents. The vibrator produces a stronger signal than a sledgehammer and we estimate its output to be around 1 kN. The frequency content of the data was concentrated at lower frequencies (<100 Hz) and the ground‐roll was far more energetic than that produced using a sledgehammer.